PEMANFAATAN EKSTRAK BUAH BELIMBING WULUH (Averrhoa Bilimbi L) SEBAGAI BAHAN PENGAWET TERHADAP UJI SENSORI DAGING BROILER - Alisiya, Melina; Septinova, Dian; Santosa, Purnama Edy (Jurnal Riset dan Inovasi Peternakan, 2018)
This study aims to determine the effect of bilimbi fruit liquid (Avverhoa Blimbli L)  towards physical quality broiler. This research carried out on March, 2017 housed in the Laboratory Animal Production and Reproduction, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The material of research used broiler meat from Karang Anyar Farm.This study used analysis descriptive based on frequency with four treatments and five replications, none of blimbi fruit (P0), bilimbi fruit liquid 20% (P1), bilimbi fruit liquid 40% (P2), and bilimbi fruit liquid 60% (P3). The observed variables are color, flavor, smell, and taste of broiler meat. Data obtained by descriptive analysis based on receiver of consumen. The result showed that the preferred concentration of bilimbi fruit for the color of raw and cooked meat was 0% and 20%, the most preferred concentration of bilimbi fruit for meat aroma was 20% for raw meat and 40% for cooked meat, meat flavor is most liked 60%. In general the preferred concentration of bilimbi fruit for the color, smell, and taste of raw or cooked meat is 20%. Keywords:broiler, bilimbi fruit liquid (Avverhoa Blimbli L), smell,  flavor.